2017
DOI: 10.1016/j.ultsonch.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of negative-charged nanoparticles assisted by ultrasound on the reversal multidrug resistance phenotype in breast cancer cells

Abstract: We have fabricated a negative-charged nanoparticle (Heparin-Folate-Tat-Taxol NP, H-F-Tat-T NP) with dual ligands, tumor targeting ligand folate and cell-penetrating peptide Tat, to deliver taxol presenting great anticancer activity for sensitive cancer cells, while it fails to overcome multidrug resistance (MDR) in MCF-7/T cells (taxol-resistant breast cancer cells). Ultrasound (US) can increase the sensitivity of positive-charged NPs thereby making it possible to reverse MDR through inducing NPs' drug release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…This reflects the higher sensitivity to enhanced sonoporation mediated by USMB exposure for MCF-7/ADR cells than MCF-7 cells, which is consistent with a previous study [31]. The underlying mechanism might involve the enhancement of cell membrane permeability and downregulation of MDR-related genes and proteins [32]. In addition, a reduction in the amount of permeability glycoprotein (P-gp) due to USMB might prevent chemotherapeutic drugs from leaving the tumor cells [33].…”
Section: Discussionsupporting
confidence: 88%
“…This reflects the higher sensitivity to enhanced sonoporation mediated by USMB exposure for MCF-7/ADR cells than MCF-7 cells, which is consistent with a previous study [31]. The underlying mechanism might involve the enhancement of cell membrane permeability and downregulation of MDR-related genes and proteins [32]. In addition, a reduction in the amount of permeability glycoprotein (P-gp) due to USMB might prevent chemotherapeutic drugs from leaving the tumor cells [33].…”
Section: Discussionsupporting
confidence: 88%
“…It can form cavitation bubbles, heat local tissues, and produce radiation force, which are used to release drugs from nanocomposites, to purify drugs and/or nanoparticles from blood vessels in tumors, and to improve drug penetration to the tumor. Wang et al 52 developed an efficient strategy to overcome multi-drug resistance (MDR) by combining negatively charged nanoparticles with US. In their study, cells are exposed to US with microbubbles prior to treatment with negatively charged Heparin-Folate-Tat-Taxol nanoparticles.…”
Section: Nanoparticle-based Cancer Therapymentioning
confidence: 99%
“…Since US can be focused, acoustic waves are easily able to deliver kinetic energy to selected small volumes deep within a human body without damaging other tissues. Therefore, physicians or physical therapists used them to stimulate healing and soften scar tissue, or high-intensity focused US—HIFU—to damage prostate cancer or break down kidney stones [ 10 , 11 , 12 , 13 ]. However, a completely new chapter in US research was opened in 1976 when a strong cytostatic effect of nitrogen mustard was observed in L1210 leukaemia cells treated with sonication without mechanical damage to cells [ 14 ].…”
Section: Introductionmentioning
confidence: 99%